Pengaruh Produk Kosmetik Yang Berlabel Halal Dan Harga Terhadap Keputusan Pembelian Di Kalangan Hijaber - Indah Datin Nadliroh,; Budi Iriani Yudaningrum, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
The purpose of this study is to assess the impact of halal-labeled cosmetic goods and pricing on hijab purchase decisions. This study relies on original data. The quantitative data acquired from a sample of 40 persons were analyzed using the SPSS software in this study. In this study, questionnaire data were used to obtain information. The normalization test, heteroscedasticity test, multiple linear regression analysis, and coefficient of determination were utilized to process the data (R2). The simultaneous test (F test) findings show that the halal label and the price on the buying decision have a Fount of 8.668. Meanwhile, from the results of the t-test (partial) of the halal label on the purchase decision, the significance value is 0.150 > 0.05. The price on the purchase decision has a significance value of 0.015 < 0.05, and the results of the determination test stated that the halal label and price were 28.2%.